A Study of the Effects of a Lateral Intake’s Positions on the Flow Pattern Around a Bridge Pier in a 180° Bend Using SSIIM2 - Niknezhad, Fariba; Mahmoudi, Amin; Vaghefi, Mohammad (Arabian journal for science and engineering (2011), 2023)
This study explored the effects of different intake positions at 45° and 90° intake angles in a 180° mild bend upon the flow pattern around a circular bridge pier using the SSIIM2 software program. Two turbulence models, the standard k – ɛ and the k – ɛ RNG, were used for numerical data validation against experimental results. Results indicated that the k – ɛ RNG turbulence model enjoyed a greater precision than the standard k – ɛ turbulence model. For all intake positions, the streamlines in the main channel, the velocity values, the average secondary flow power and the shear stress remained almost the same after the intake angle was changed from 45° to 90°. However, the streamlines in the intake channel were different. The average secondary flow power increased by about 41.2% with the intake placed in the second half of the bend compared to the first half, and it increased by 17.6% when the intake was placed in the 115° position and no piers were involved.